2019
DOI: 10.1016/j.jtho.2019.08.1677
|View full text |Cite
|
Sign up to set email alerts
|

P2.09-28 Prognostic Impact of LKB1 Expression in Advanced Non-Small-Cell Lung Cancer

Abstract: (IHC) clone which has higher sensitivity and specificity (SP384) is available. The aim of this study is to compare these ROS1 antibodies and to interpret with FISH results. Method: Twenty-three patients (fourteen ROS1 FISH-positive, nine ROS1 FISH-negative) were included for this study. The material available for all tumors had been formalinfixed and paraffin-embedded (FFPE). D4D6 clone from Cell Signaling Technology and SP384 clone were provided by Ventana Medical Systems, which were used for ROS1 expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Moreover, it is important to highlight that an LKB1 variation is different from the loss of LKB1 protein expression, the latter of which being the alteration we tested. Interestingly, a study in Italy previously identified negative LKB1 expression by immunohistochemistry in 66% (65 of 98) of patients with non–small cell lung cancer (NSCLC), and similarly, a study performed in our population identified this result in 65 of 87 patients (75%) with NSCLC …”
supporting
confidence: 69%
“…Moreover, it is important to highlight that an LKB1 variation is different from the loss of LKB1 protein expression, the latter of which being the alteration we tested. Interestingly, a study in Italy previously identified negative LKB1 expression by immunohistochemistry in 66% (65 of 98) of patients with non–small cell lung cancer (NSCLC), and similarly, a study performed in our population identified this result in 65 of 87 patients (75%) with NSCLC …”
supporting
confidence: 69%